Microstructure evolution of homoepitaxial MgO layer and the effect on the growth mode of CeO2 film. Issue 17 (1st December 2019) - Liu, Shunfan; Wang, Wei; Liu, Linfei; Zheng, Tong; Li, Yijie
Abstract: Using pulsed laser deposition technique, highly c -axis oriented CeO2 film with the in-plane full width of half maximum (FWHM) value of 2.78° was fabricated on the homoepitaxial MgO (homo-MgO) layer for the first time. Interestingly, the quality of the CeO2 film was inconsistent with the homo-MgO film. To explain the puzzling finding, the growth mechanism of CeO2 on the homo-MgO films had been illustrated. The potential barrier caused by large value of roughness was put forward to explain the appearance of the CeO2 (111) peak. In addition, by the interaction of MgO film's texture and surface roughness, the reason why a higher quality of CeO2 film obtained under the P s of 70 W was clarified in detail. In the end, we presented compelling evidence to prove the reason why the c -axis oriented CeO2 film can grow on the IBAD-MgO substrate.